Value creation from e-business models - Currie, Wendy, 1960- (Oxford : Butterworth-Heinemann, 2004)
Value Creation from E-Business Models provides a thorough analysis of what constitutes an e-business model. Unlike many e-business books available, this text draws together theoretical and empirical contributions from leading academic scholars in the field of management information systems. Divided into four parts, E-Business Models and Taxonomies; E-Business Markets; E-Business Customer Performance Measurement; and E-Business Vendor Applications and Services, this book is the critical dissection of E-Business that today's academic community needs. * World class academic contributors brought together in one volume * Demonstrates that there are e-business models which create value for customers and vendors alike * Learn from the lessons of the past five years in developing and implementing e-business models.
Value-creation from e-business models : issues and perspectives / Wendy L. Currie -- Business models and their relationship to strategy / Peter B. Seddon ... [et al.] -- A framework for codifying business models and process models in e-business design / Philip Joyce and Graham Winch -- An ontology for e-business models / Alexander Osterwalder and Yves Pigneur -- e-Business value modelling using the e³-value ontology / Jaap Gordijn -- A causal network analysis of e-market business models / Jon Moon -- Knowledge management and e-commerce : when self-service is not the sensible solution / Sue Newell and Jimmy Huang -- Perceptions of strategic value and adoption of e-commerce : a theoretical framework and empirical test / Elizabeth E. Grandβon and J. Michael Pearson -- Value creation from corporate web sites : how different features contribute to success in e-business / Nils Madeja and Detlef Schoder -- Evaluating the quality of e-business implementation with E-Qual / Stuart Barnes and Richard Vidgen -- The e-sourcing opportunity : from projects and ASPs to value networks / Leslie P. Willcocks and Robert Plant -- Value creation in application outsourcing relationships : an international case study on ERP outsourcing / Erik Beulen and Pieter Ribbers -- NHS information systems strategy, planning and implementation of primary service provision / Matthew W. Guah -- A framework of integrated models for supply chain e-management / Charu Chandra, Sameer Kumar and Alexander V. Smirnov -- Building out the Web services architecture : the challenge of software applications integration / Wendy L. Currie.
Includes bibliographical references and index.
Keywords: Electronic commerce; Business -- Mathematical models; Electronic books